Peran FKUB Kota Bandung dalam Counter-Radikalisme melalui Pendekatan Dakwah berbasis Teologi Komparatif dan Komunikasi Lintas Agama - Lukman, Dede; Abdul Ghani, Agi Muhammad; Shola, Rama Adilla (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2025)
Religious radicalism has become a serious threat to social stability and inter-religious harmony. This phenomenological study examines the role of the Bandung City Religious Communication Forum (FKUB) in implementing counter-radicalism strategies through Islamic da'wah based on comparative theology and interfaith communication. FKUB Bandung City successfully built multi-religious consensus regarding the dangers of extremism by integrating theological understanding from various religious traditions. Da'wah strategies are implemented through internal and external communication, including formal programs such as dialogue and counseling, as well as informal initiatives in the form of campaigns and social activism. FKUB's anti-radicalism da'wah implementation uses a multi-platform approach, combining offline activities with digital media utilization to expand message reach. This research uses the constructivism paradigm using philosophical and psychological approaches through phenomenological research methods. The collection of primary data in this study was obtained through interviews, secondary data obtained through observations and documents available in the field and tertiary data related to relevant literature that can support the findings in this study. Data analysis involves bracketing, dialogue with individual participants, reflection on research results, identifying themes and then building descriptions and concepts. Analysis shows communication effectiveness at three levels: micro (internalization of individual values), meso (formation of communal cooperative attitudes), and macro (development of transcendental understanding based on universal values). This research recommends the importance of continuous synergy between academics, policymakers, and religious leaders in strengthening FKUB's capacity. Government support for infrastructure and budget, as well as active participation of religious figures in spreading anti-radicalism messages, are key to the success of interfaith dialogue-based deradicalization programs.